Solution A1 is correct hope it helpsss
I cant even see the picture clearly
Answer:
ubeovgtnwjggswgtepibvqyytkhfhduygvtqyaccjvgvdbbetedgtdgyegghjgdbecdkbfbgdhebhjegeckgbkhbeiubuvvsakvhfe
Step-by-step explanation:
hrtrrrrrrrrrrrrrrrrhhhhhhrhhhhhhhhhhhhhhhhhhhhhhhhhhhhrhhrhhrrhhhrhhhhh
Sin2(x) +cos(x)=1
from the relation: (sin2(x) +cos2(x) =1 )
so , sin2(x)=1-cos2(x)
by subs. in the main eqn.
1-cos2(x) + cos(x) =1
by simplify the eqn.
cos(x) -cos2(x)=0
take cos(x) as a common factor
cos(x)* (1-cos(x))=0
then cos(x)=0 && cos(x)=1
cos(x)=0 if x= pi/2
& cos(x) = 1 if x = 0 , 2*pi
so the solution is x= {0,pi/2 , 2*pi}
A I think
Step-by-step explanation:
I'm not 100% sure though